A Research Note : More to Ponder on the Perspectives of Sustainability of Tourism Destinations - R., Sabari Shankar (Indian Journal of Marketing, 2021)
This research note focused on tapping the research opportunities on the perspectives of sustainability on tourism destinations. Being a short communication, the research note was created using the literary sources that concentrated only on the sustainability of tourism destinations. Growing tourism attributes ; need for positioning destinations in competitive industrial markets; rapid changes in tourism market characteristics, motives, and opportunities ; and mainly to sustain the tourism resources for better future consumption and preservation were the primitive forces to undertake the research note, which would facilitate further research works in the arena. The communications highlighted the integral and in-depth aspects such as centrality of sustainability, tourists’ knowledge about sustainability, tourists’ responsibility towards sustainability of destinations and natural resources, destination behavior towards sustainability, blending culture and sustainability, and rural destinations and their relevance on a sustainable future. Beneficial keynotes for policy makers and others thereof were enumerated throughout the note.